Низкоэмиссионные и терморегулирующие покрытия на основе тонких слоев серебра; Известия вузов. Физика; Т. 55, № 11/2 - Асаинов О. Х. Олег Хайдарович; Баинов Д. Д. Даши Дамбаевич; Кривобоков В. П. Валерий Павлович; Пащенко О. В. Олег Валентинович; Юдаков С. В. Сергей Владимирович (2012, 2012)
Заглавие с экрана